Comparative Efficacy and Safety of Thrombopoietin Receptor Agonists in Adults With Thrombocytopenia: A Systematic Review and Network Meta-analysis of Randomized Controlled Trial - Deng, Junzhu; Hu, Haiyang; Huang, Feihong; Huang, Chunlan; Huang, Qianqian; Wang, Long; Wu, Anguo; Yang, Jing; Qin, Dalian; Zou, Wenjun; Wu, Jianming (Frontiers in Pharmacology, 2021)
Thrombopoietin receptor agonists (TPO-RAs) play a crucial role in stimulating thrombopoiesis. However, conventional meta-analyses have shown inconsistent results regarding the efficacy of thrombopoietin receptor agonists. Therefore, we performed a network meta-analysis to assess the effects of five TPO-RAs via direct and indirect comparison. For this network meta-analysis, we considered randomized trials that included any of the following interventions: avatrombopag, lusutrombopag, eltrombopag, romiplostim, recombinant human thrombopoietin (rhTPO)+rituximab, rituximab, and placebo. We searched the Medline, PubMed, Embase, the Cochrane Library, and Web of Science databases for randomized controlled trials from inception to January 31, 2021. The primary outcome was the number of patients achieving platelet response (platelet count ≥ 50 × 109/L), and the secondary outcome was the therapy-related serious adverse events and incidence of bleeding episodes. We performed a random-effects network meta-analysis to obtain the estimates for primary and secondary outcomes and presented these estimates as odds ratios with 95% confidence intervals. We ranked the comparative effects of all drugs against the placebo using surface under the cumulative ranking probabilities. In total, 2207 patients were analyzed in 20 clinical trials. All preparations improved the point estimates of platelet response when compared with the placebo. Avatrombopag and lusutrombopag were the best compared to the placebo; the former had a non-significant advantage compared to the latter (odds ratio (OR) = 1.91 (95% confidence interval: 0.52, 7.05)). Both treatments were superior to eltrombopag, romiplostim, rituximab, and rhTPO+rituximab, with corresponding ORs of 3.10 (1.01, 9.51), 9.96 (2.29, 43.29), 33.09 (8.76, 125.02), and 21.31 (3.78, 119.98) for avatrombopag and 1.62 (0.63, 4.17), 5.21 (1.54, 17.62), 17.34 (5.15, 58.36), and 11.16 (2.16, 57.62) for lusutrombopag. Regarding bleeding, the placebo group had the highest probability of bleeding, whereas lusutrombopag had the lowest risk for any bleeding when compared to the placebo. The incidence of adverse events in patients treated with rituximab was slightly higher than that in patients treated with placebo or other treatments. Overall, this meta-analysis showed that avatrombopag may yield the highest efficacy because it has the most favorable balance of benefits and acceptability.